Drug utilization pattern in four major wards of a tertiary hospital in eastern Nepal (Health Renaissance, 2017)
Background: Drugs play an important role in protecting, maintaining and restoring health. Drugs are prescribed irrationally throughout the world.Objective: To study the utilization of drugs in in-patient of four major ward of a tertiary care hospital in Nepal.Method: This was a cross-sectional descriptive study conducted in four major wards for duration of one month.Result: A total of 467 patients were prescribed a total of 2188 drugs among which 535 drugs were prescribed in surgery ward, 567 drugs in medicine ward, 220 drugs in pediatric ward and 866 drugs in obstetrics and gynecology ward. The average number of drugs per prescription was 4.68. All drugs were prescribed by brand names and generic prescribing was nil. Among all, 70.61% of drugs were from essential list of drugs.43.87% of drugs were given through injections. 34.41%, 26.05%, 11.7%, 6.35%, 6.17% and 4.84% of prescribed drugs were AMA, GIT, MSK, CNS, CVS and minerals and vitamins respectively. Four drugs per prescription were prescribed to 21.41% of the total patients (n=467).Conclusion: Polypharmacy, low rate of generic prescriptions and overuse of antibiotics still remain a problem in health care facilities in Nepal. This calls for sustained interventional strategies and periodic audit at all levels of health care to avoid the negative consequences of inappropriate prescriptions.Health Renaissance 2015;13(2): 50-65